DLST-dependence dictates metabolic heterogeneity in TCA-cycle usage among triple-negative breast cancer - Ning Shen (Nature Portfolio, 2021)
Shen and Korm et al. investigate the role of dihydrolipoamide S-succinyltransferase (DLST), a tricarboxylic acid (TCA) cycle enzyme, in the metabolic heterogeneity of triple negative breast cancer (TNBC) cell lines. They show that either depletion or inhibition of DLST in the dependent cells leads to decreased invasion and metastasis in vitro and in vivo.